2017
DOI: 10.18356/74992ef2-en
|View full text |Cite
|
Sign up to set email alerts
|

Does product diversification and emphasis on profitability in microfinancing alleviate poverty?

Abstract: Microfinancing institutions (MFIs) are likely to change their management policies and focus more on profitability and product diversification as they mature and expand in size because of a number of reasons, including among them, donor pressure and/or lack of funding to expand. The present study empirically tests whether such changes occur in MFIs over time and how these changes affect their performance with regard to alleviating poverty. Using data from a sample of 234 MFIs from around the world, including in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The results showed that product diversi cation by MFIs had a positive impact on the outreach. Thereby, this showed the diversi cation of health care support activities contribute to advance the health care services outreach of MFIs [27]. Many MFIs diversi ed to offer the services, i.e, product diversi cation such as type of different non-nancial services offered by formal MFIs.…”
Section: The Health Care Services Outreachmentioning
confidence: 98%
“…The results showed that product diversi cation by MFIs had a positive impact on the outreach. Thereby, this showed the diversi cation of health care support activities contribute to advance the health care services outreach of MFIs [27]. Many MFIs diversi ed to offer the services, i.e, product diversi cation such as type of different non-nancial services offered by formal MFIs.…”
Section: The Health Care Services Outreachmentioning
confidence: 98%
“…Rwanda's real estate market has been growing steadily, especially in Kigali, the capital city. The country's stability and ease of doing business have attracted investors, leading to increased commercial and residential development (Nanayakkara & Mia, 2017) The property market in Kenya is reacting to demand that has been created by the expanding middle class with disposable income, in which people have become able to buy homes and others service their mortgages (Makhoha, Namusonge & Sakwa, 2016). This boom in the real estate sector began somewhere in the mid to late 2000s.…”
Section: Introductionmentioning
confidence: 99%